Cost-effectiveness analysis of amivantamab plus chemotherapy versus chemotherapy alone in NSCLC with EGFR Exon 20 insertions - Yue, Ping; Zhang, Mengwei; Feng, Yuanying; Gao, Yuan; Sun, Chao; Chen, Peng (Frontiers in Oncology, 2024)
Objective Amivantamab plus chemotherapy has been proved to be an efficient treatment strategy for non–small-cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) exon 20 insertions. The aim of this study was to conduct the cost-effectiveness analysis of amivantamab-chemotherapy compared with chemotherapy alone in NSCLC harboring EGFR exon 20 insertion mutations. Methods We constructed a Markov model based on the data derived from the PAPILLON trial. We evaluated the cost, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were used to evaluate the influence of different parameters on this model. Results Compared with chemotherapy alone, amivantamab combined with chemotherapy treatment gained an incremental effectiveness of 0.473 QALYs and an incremental cost of 361,950.952, which resulted in an ICER of 765,224/QALY. The ICER was much higher than the willingness-to-pay threshold of 15,0000/QALY. One-way sensitivity analysis revealed that amivantamab cost was the leading influential factor in the model. Conclusions Compared with chemotherapy alone, amivantamab plus chemotherapy is not a cost-effective first-line treatment choice for NSCLC patients with EGFR exon 20 insertions. The costly price of amivantamab is one of the major reasons for the high cost of this combined treatment strategy. Therefore, it is imperative to take into account the high cost of amivantamab in the subsequent clinical application and strive to attain a relative equilibrium between its significant clinical benefit and economic encumbrance.